Efficacy and safety of intermittent theta burst stimulation versus high-frequency repetitive transcranial magnetic stimulation for patients with treatment-resistant depression: a systematic review - Lan, Xian-Jun; Yang, Xin-Hu; Qin, Zhen-Juan; Cai, Dong-Bin; Liu, Qi-Man; Mai, Jian-Xin; Deng, Can-jin; Huang, Xing-Bing; Zheng, Wei (Frontiers in Psychiatry, 2023)
Objective: Intermittent theta-burst stimulation (iTBS), which is a form of repetitive transcranial magnetic stimulation (rTMS), can produce 600 pulses to the left dorsolateral prefrontal cortex (DLPFC) in a stimulation time of just over 3 minutes.The objective of this systematic review was to compare the safety and efficacy of iTBS and high-frequency (≥ 5 Hz) rTMS (HF-rTMS) for patients with treatment-resistant depression (TRD).Methods: Randomized controlled trials (RCTs) comparing the efficacy and safety of iTBS and HF-rTMS were identified by searching English and Chinese databases. The primary outcomes were study-defined response and remission.Results: Two RCTs (n=474) investigating the efficacy and safety of adjunctive iTBS (n=239) versus HF-rTMS (n=235) for adult patients with TRD met the inclusion criteria. Among the two included studies (Jadad score=5), all were classified as high quality. No group differences were found regarding the overall rates of response (iTBS group: 48.0% versus HF-rTMS group: 45.5%) and remission (iTBS group: 30.0% versus HF-rTMS group: 25.2%) (all Ps>0.05). The rates of discontinuation and adverse events such as headache were similar between the two groups (all Ps>0.05).The antidepressant effects and safety of iTBS and HF-rTMS appeared to be similar for patients with TRD, although additional RCTs with rigorous methodology are needed.